Analysis and personal reflection of the transition to electrification of quattro motors through innovation - Rodrigues, João Diogo Aurélio Duarte (2023)
This work project presents an analysis on the transition to electrification of the fictional car company “Quattro Motors” in the business simulation, and a personal reflection on how this experience as the Innovation Director resulted in the questioning my interpersonal skills and performance. The first section is a description of the company and on three corporate functions: Innovation, Operations and Marketing. The second section is a personal reflection on how the experience affected me, focusing on two separate critical incidents: the decision making on the last Innovation’s investment, and the launch of the micro car.